PENGETAHUAN MENENTUKAN PEMBERIAN ASI EKSKLUSIF - Fitria Ayuningtyas, Ika (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: The decline in infant mortality is one of the important indicators to measure the success of health development. Various attempts have been made to reduce infant mortality by promoting exclusive breastfeeding. Indonesian Demographic Health Survey (IDHS) year 2003 mentioned that the coverage of exclusive breastfeeding was only 40%; this condition was far from the national target by 80%. Mother's ability to breastfeed should be prepared from pregnancy, especially the second trimester and third trimester. The content of breast milk (ASI) gives a huge benefit for the baby. Breast milk contains balanced nutrition in quantity and quality. The composition of nutrients contained in breast milk is very precise and ideal for the development of the child. In addition, the well-maintained composition of breast milk also makes infants and children healthy. Mother’s knowledge on exclusive breastfeeding affects maternal behavior in exclusively breastfeeding their children. Objective: This study aimed to determine the relationship of the level of mother’s knowledge about exclusive breastfeeding to breastfeeding. Methods: This was a descriptive analytic study with a cross sectional approach. The research was conducted in BPS (privately practicing midwife) Endang Purwaningsih of Bantul in September 2009- February 2010. The samples in this study were some of the mothers who had children aged > 6 months as many as 30 mothers. The instrument used a questionnaire. Data analysis used Chi-square. Results: The level of mother’s knowledge on exclusive breastfeeding was mostly good (43.3%) and infants who were exclusively breastfed was 60%. From the analysis of the chi-square test, the value of p= 0.04 (p <0.05), with a correlation coefficient of 0.41. Conclusion: There was a significant relationship between the level of mother's knowledge on exclusive breastfeeding and exclusive breastfeeding. The correlation between the two variables was positive with a moderate degree of closeness in the relationship. Mother’s knowledge about exclusive breastfeeding needs to be upgraded to the success of exclusive breastfeeding. Keywords: Knowledge, breastfeeding, exclusive breastfeeding